Dauru Al-Bi’ati Al-Lughowiyati As-Sakaniyati fi Ta’allumi-l-Lughoti Al-‘Arabiyati li Tholibati Al-Fasli Al-Awali bi Ma’hadi Darissalam Gontor li-l-Banati Al-Haram Al-Awwal - Fatayati, Umma; Diannita, Rindang; Setyo Rini, Fitri; Nailun Ni’mah, Faricha (Ukazh: Journal of Arabic Studies, 2024)
اهتم معهد دار السلام كونتور للبنات الحرم الأول نحو اللغة العربية والإنجليزية كوسيلة الاتصال والتفاعل اليومي. وجدت الباحثة بعض الصعوبات الموجهة في تعلم اللغة العربية كصعوبة في تعويد الطالبات على التواصل والتفاعل الإجابي باللغة العربية. أن هدفا البحث هو الكشف عن دور البيئة اللغوية السكنية في تعلم اللغة العربية لطالبات الفصل الأول بمعهد دار السلام كونتور للبنات الحرم الأول استخدمت الباحثة بحثا ميدانيا ودراسة وصفية كيفية، وأربعة أساليب جمع البيانات، منها: الملاحظة، والمقابلة، والتوثيق، والتثليث. وأسلوب تحليل البيانات المستخدم هو نموذج مايلز وهوبرمان (Miles and Huberman), الذي يتضمن على ثلاث خطوات، وهي: تخفيض البيانات، وعرض البيانات، وخلاصة. أن نتيجة هذا البحث هي أن البيئة اللغوية السكنية لطالبات الفصل الأول شاملا وكاملا ورائعا. والبيئة اللغوية السكنية ذات دور هام في تعلم اللغة العربية لطالبات الفصل الأول نحو أربع مهارات لغوية كتعويد سماعة الأصوات العربية وفهم المسموع، ووتعويد على النطق والتفاعل الإيجابي باللغة العربية، وتعويد على القراءة الصحيحة وفهم مضمون الكتابة العربية، وممارسة على كتابة النصوص العربية الصحيحة The Modern Islamic Boarding School Darussalam Gontor is an educational institution that utilizes Arabic and English as the primary languages of instruction on a daily basis. One of the main challenges in teaching Arabic, particularly for Student of class one, is encouraging them to actively speak the language. This study aims to examine the role of the language environment in the Arabic learning process for first-year students at the Darussalam Gontor Modern Islamic Boarding School (1st Campus). The research method employed is descriptive qualitative, with data collection techniques including observation, interviews, documentation, and triangulation. The data analysis follows the Miles and Huberman model, which consists of three stages: data reduction, data presentation, and conclusion drawing and verification. The findings indicate that the language environment at Darussalam Gontor Putri 1 Modern Pondok meets the ideal criteria for a conducive and effective language environment. It plays an active role in supporting the language learning process, particularly for Student of class one, across all four language skills: habituating students to listen to and comprehend Arabic contexts, encouraging active interaction in Arabic, promoting reading and understanding of Arabic sentences and vocabulary, and training students to write Arabic sentences correctly and appropriately.